Displacement and Debt: The Role of Debt in Returning to Work in the Period Following the Great Recession - Robert W. Bednarzik; Andreas Kern; John J. Hisnanick (Institute of Labor Economics (IZA), 2017)
The onset of the housing and subsequent financial crisis in 2008 marked the steepest economic downturn in the United. States, since the Great Depression in the late 1920s and 1930s. This most recent financial crisis has been characterized by massive layoffs and displacement. Given the depth of the recent 'great' recession and its links to the finance and housing industries, both economists and policy analysts have speculated that the sticky jobless situation for many would-be workers is also related to their level of individual and/ or household debt. In contrast to a growing literature that links financial market conditions on employers' hiring capabilities, we focus on the question how household indebtedness renders households' incentives to search for and take up a new job after displacement? Using information on households' labor market and financial behavior from the Survey
Keywords: J2; G1; 330; unemployment; debt; dislocated workers